HAK ASASI MANUSIA (HAM) PERSPEKTIF HUKUM ISLAM - Rusdin Muhalling (Al-'Adl, 2018)
The focus of the study is Human Rights (HAM) Perspective of Islamic Law. Human rights perspective of Islamic law is more universal and humane, the basic principles of human rights enforcement in the perspective of Islamic law can only be realized, if the formation, formulation, regulation in the field of law by law enforcement officers in Indonesia refers to Islamic law. The purpose of this research is to study and analyze the human rights perspective of Islamic law, with a normative, jurudic and socilogical theological approach. Human rights as a gift from God Almighty are basic rights that naturally attach to human beings and include: the right to live properly, the right to embrace religion and worship according to their respective religions, the right to have a family and to obtain offspring through a legal marriage, the right to education, the right to do business, private property, the right to obtain legal certainty and equality in law, justice and security, the right to express opinions, associate and gather.